How children learn the meanings of words - Bloom, Paul, 1963- (Learning, development, and conceptual change., 2000)
"According to Paul Bloom, children learn words through sophisticated cognitive abilities that exist for other purposes. These include the ability to infer others' intentions, the ability to acquire concepts, and appreciation of syntactic structure, and certain general learning and memory abilities. The acquisition of even simple nouns requires rich conceptual, social, and linguistic capacities interacting in complex ways." "This book requires no background in psychology or linguistics. Topics include the effects of language on spatial reasoning, the origin of essentialist beliefs, and the young child's understanding of representational art. The book should appeal to general readers interested in language and cognition as well as to researchers in the field."--Jacket